The Relationship Between Tumor Size Parameters and Carcinoembryonic Antigen (CEA) Levels in Colorectal Adenocarcinoma Based on Contrast-Enhanced Abdominal CT Scan - Prasatya, Dewa Putu Jaya; Margiani, Ni Nyoman; Wijaya, I Gusti Agung Gede Mahendra; Putra, I Wayan Gede Artawan Eka (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2025)
Introduction: Colorectal adenocarcinoma is a common malignancy with high mortality. Carcinoembryonic Antigen (CEA) is widely used as a tumor marker, while contrast-enhanced CT scans provide tumor size parameters. The correlation between these parameters and CEA remains unclear. Objective: To analyze the relationship between tumor area and thickness on contrast-enhanced CT scan and CEA levels in colorectal adenocarcinoma. Methods: A retrospective cross-sectional study was conducted at RSUP Prof. Dr. I.G.N.G. Ngoerah (2018–2023) involving patients with available CT scan and CEA data. Pearson correlation and multivariate regression were applied. Results: Tumor area showed a significant positive correlation with CEA (r = 0.513; p = 0.001), independent of age and sex. Tumor thickness was not significantly correlated (r = 0.196; p = 0.224). Conclusion: Tumor area correlates significantly with CEA levels, whereas tumor thickness does not. Tumor area may serve as an additional indicator in colorectal cancer evaluation.